Nonequilibrium quantum battery based on quantum measurements - Jianying Du; Yanjiang Guo; Baowen Li (Physical Review Research)
We propose and analyze the charging and discharging processes of measurement-assisted quant um batteries, exploring how different measurement schemes affect their performance. It is found that applying projective measurements with a general basis and optimizing the measurement parameters can enhance the battery's performance, including increases in both charging energy and ergotropy. Compared to local measurement schemes, the quantum battery exhibits significantly improved performance under nonlocal measurement schemes. However, this performance improvement comes at the cost of higher resource expenditure in nonlocal schemes. Additionally, the quantum battery can function as a quantum energy source, driving the qubit-resonator system to facilitate energy pumping. Our findings provide deeper insights into the fundamental properties of quantum batteries driven by quantum measurements, offering a pathway toward the design of more efficient and controllable quantum battery systems.